A picture is worth a thousand words: portraying language learning experiences in a bilingual school in Honduras - Bettney, Esther (Colombian Applied Linguistics Journal, 2017)
This qualitative study explored the experience of students learning English in an early partial one-way immersion program in Honduras. While immersion research is well-established in various parts of the world, scarce research has focused on programs in Central America. It is important to consider this geographical context as models of bilingual education must be adapted to the local student population (de Mejía, 2002). To address this research gap, written reflections were collected from 203 Grades 1 to 11 students in a one-way immersion program. Through pictures and words, students portrayed their experiences learning English. Two main themes emerged: 1) students’ views of their language learning process, and 2) perceived factors which contributed to the learning of English. These themes are discussed in light of key immersion research on student language proficiency, maximizing output, and meaningful language use. This study confirmed results from other immersion studies in certain areas such as the importance of maximizing output, while also demonstrating the importance of continuing to explore students’ learning experiences within the Latin American context.